Limbic system hyperactivity and the phenomena of spiritual awakenings. Confronting the supernatural through the neural networks - Nyske, Ewelina (Humaniora. Czasopismo Internetowe, 2020)
Spiritual awakenings tend to be associated with the religious rapture regardless of the spiritual path one decides to follow and are defined as temporary experiences whose main characteristic is the intensified sense of unity with the sacred. The nature of these particular phenomena gives rise to the need to carry out the in-depth analysis of the human responsiveness pattern in relation to the external stimuli, especially within the context of a religious experience. The limbic system, believed to be the headquarters of human emotions, tends to be easily activated, both verbally and non-verbally, and such activation may influence human behavior to a great extent. The principal objective of this paper is to provide a detailed classification of awakening experiences as well as to focus on the role of the amygdala and hippocampus in the production of particular religious experiences such as spiritual visions, speaking in the tongues or astral projections.